2016
DOI: 10.1002/jez.b.22719
|View full text |Cite
|
Sign up to set email alerts
|

Genome Compositional Organization in Gars Shows More Similarities to Mammals than to Other Ray‐Finned Fish

Abstract: Genomic GC content can vary locally, and GC-rich regions are usually associated with increased DNA thermostability in thermophilic prokaryotes and warm-blooded eukaryotes. Among vertebrates, fish and amphibians appeared to possess a distinctly less heterogeneous AT/GC organization in their genomes, whereas cytogenetically detectable GC heterogeneity has so far only been documented in mammals and birds. The subject of our study is the gar, an ancient "living fossil" of a basal ray-finned fish lineage, known fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…Moreover, Symonová et al. () demonstrated that gars and bowfin differ in intrachromosomal organization. The application of cytogenetic approaches and bioinformatics analyses revealed genome AT/GC heterogeneity in spotted gar genome (Symonová et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Symonová et al. () demonstrated that gars and bowfin differ in intrachromosomal organization. The application of cytogenetic approaches and bioinformatics analyses revealed genome AT/GC heterogeneity in spotted gar genome (Symonová et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Lepisosteiformes represent higher chromosomal counts than bowfin and teleosts. The tropical gar (2n = 56) and the spotted gar (2n = 58) demonstrates difference in 2n by a fusion/fission event of one chromosome pair Symonová et al (2017). Since gars did not undergo the TGD (Amores et al, 2011), their higher chromosomal counts related to teleost were explained by chromosome fusions in the lineage leading to teleosts after divergence from gar but before the TGD .…”
Section: Cytotaxonomic Comparison Of Bowfin With Major Lineages Of Acmentioning
confidence: 99%
“…Symonova et al. () performed cytogenomic analyses that revealed a unique GC content compartmentalization in gars compared with other ray‐finned fishes and that curiously resemble similar patterns observed in mammals.…”
mentioning
confidence: 83%
“…Moreover, due to the homogeneity in base composition common to genomes of poikilothermic organisms [Medrano et al, 1988], Gbanding in fish chromosomes is not comparable with the distinct patterns produced in mammals [Symonová et al, 2016]. Still, sometimes it is possible to use conventional banding methods for chromosome identification in fish [Gold et al, 1990], as acceptable differentially stained patterns of chromosomes can be obtained [Wiberg, 1983;Symonová et al, 2016]. In these cases, the detailed standardization of a karyotype with unequivocal identification of individual chromosome pairs can be achieved by a combined use of conventional cytogenetic approaches and physical mapping as it was done in mammalian species with high chromosome numbers [Breen, 2008] or in species with complex genomes with different ploidy levels [Trifonov et al, 2015].…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%
“…Karyotype standardization is complicated by the high chromosome numbers with the prevalence of small elements in the set. Moreover, due to the homogeneity in base composition common to genomes of poikilothermic organisms [Medrano et al, 1988], Gbanding in fish chromosomes is not comparable with the distinct patterns produced in mammals [Symonová et al, 2016]. Still, sometimes it is possible to use conventional banding methods for chromosome identification in fish [Gold et al, 1990], as acceptable differentially stained patterns of chromosomes can be obtained [Wiberg, 1983;Symonová et al, 2016].…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%